The antimicrobial activity of peppermint (Mentha piperita) and pennyroyal (Mentha pulegium) essential oil on three mastitis-causing pathogens in milk - Reza Rahchamani; Javad Bayat Kouhsar; Samira Noori (The Iranian Journal of Veterinary Science and Technology, 2023)
Bovine mastitis causes a lot of economic losses, and the appearance of resistant strains of bacteria has led to the use of alternative natural bioagents for treatment. It is generally believed that high levels of fat and/or protein in foods may protect bacteria against the effects of essential oils (EOs). The purpose of this paper was to investigate the effect of EOs of Mentha piperita (peppermint) and Mentha pulegium (pennyroyal) on three bovine mastitis bacteria (Escherichia coli, Streptococcus agalactiae, and Staphylococcus aureus) in milk. Gas chromatography/mass spectrometry was used for the analysis of EOs. Antibacterial effects of the EOs on bacteria were evaluated with minimum bactericide concentration (MBC), minimum inhibitory concentration (MIC), and time-kill assay. Major components of peppermint EO were carvone (63.02%) and limonene (24.48%), and those of pennyroyal EO were pulegone (48.16%), eucalyptol (14.57%), and piperitenone (10.09%). The MIC and MBC were 0.62% and 1.25% for pennyroyal, 0.31-1.25% and 0.62-2.5% for peppermint, 0.31-0.62% and 0.62-2.5% for peppermint and pennyroyal, respectively. At 6-h, the bacterial reduction of treatments compared to the control group was significant for E. coli and S. agalactiae bacteria. The S. agalactiae and S. aureus counts significantly decreased in the peppermint and pennyroyal group at 24-h. In conclusion, peppermint and pennyroyal EO showed an antibacterial effect on these three bacteria and can be evaluated as an adjunct or alternative to antibiotics in the treatment of bovine mastitis.